Kevalidan dan Respon E-Modul Interaktif Berbasis Aplikasi Android pada Siswa Kelas XI SMA Negeri 4 Musi Rawas - Ayu Angraena; Wahyu Arini (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to develop an Android Application-Based Interactive E-Module to Increase Interest and Learning Outcomes of Physics Students of Class XI SMA Negeri 4 Musi Rawas which is valid, practical and effective. This type of research is research and development (R & D) with the development model used, namely ADDIE (analysis, design, development, implementation, and evaluation). The research sample or research subjects were students of class XI SMA Negeri 4 Musi Rawas students who were taken by simple random sampling technique. Data was collected by using questionnaires and tests. The validation carried out got results in a very good category, with a total score of 176. Student responses to the android application-based e-module were with a score of 88.23 which obtained a score of strongly agree. In addition, from the results of the tests carried out, an average value of 79,73 was obtained with tcount = 2,448 and ttable = 2.060 because tcount ttable then Ha was accepted and the average percentage of student activity during the practicum was 83.38% included in the very high category. So it can be said that the interactive e-module based on the android application that was developed was valid, practical, and effective.